STABILITY AND BIFURCATION OF PERIODIC MOTIONS OF THE PERMANENT MAGNET ROTOR SYSTEM WITH RUBBING - LAN HongWei (Jixie qiangdu)
Established a two degrees of freedom model with discontinuous rigidity and damp for studying the response of the permanent magnet motor’s rotor and stator rubbing system,and there are abundant nonlinear dynamic behaviors when rubbing.the stability of periodic motions and the transitions to chaos though period-doubling bifurcations or Hopf bifurcations are studied based on Poincare mapping. In view of the case of multi-parameters,their influences on the bifurcation behaviors and chaos motions of rotor and stator rubbing system are analyzed in detail. The analyzed results provide theoretical bases for safely,steadily,unfailingly operating on high speed,and quicken the motor developments toward high speed.